"Why would you want to stand?" an account of the lived experience of employees taking part in a workplace sit-stand desk intervention - Jennifer Hall; Tess Kay; Alison McConnell; Louise Mansfield (BMC, 2019)
Abstract Background Sit-stand desk interventions have the potential to reduce workplace sedentary behaviour and improve employee health. However, the extent of sit-stand desk use varies between employees and in different organisational contexts. Framed by organisational cultural theory and product design theory, this study examined employees' lived experience of taking part in a workplace sit-stand desk intervention, to understand the processes influencing feasibility and acceptability. Methods Participant observations and qualitative interviews were conducted with 15 employees from two office-based workplaces in the UK, as part of a process evaluation that ran alongside a pilot RCT of a workplace sit-stand desk intervention. Observational field notes and transcripts were analysed using thematic analysis. Results Three themes related to the experience of using a sit-stand desk at work were generated: employees' relationship with their sit-stand desk; aspirations and outcomes related to employee health and productivity; and cultural norms and interpersonal relationships. The perceived usability of the desk varied depending on how employees interacted with the desk within their personal and organisational context. Employees reported that the perceived influence of the desk on their productivity levels shaped use of the desk; those who perceived that standing increased energy and alertness tended to stand more often. Sit-stand desks were voiced as being more acceptable than intervention strategies that involve leaving the desk, as productivity was conflated with being at the desk. Conclusions The findings indicate a range of organisational, social-cultural and individual-level factors that shape the feasibility and acceptability of sit-stand desk use, and suggest strategies for improving employees' experiences of using a sit-stand desk at work, which might positively influence sedentary behaviour reduction and health. Trial registration Clinicaltrials.gov identifier NCT02172599, 22nd June 2014 (prospectively registered).